Concept of root resection of single rooted teeth: Case report with 8-months follow-up - Amit Arvind Agrawal (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
Purpose: We have a high percentage of ageing population that is extensively restored. As the number of restorations will increase so will the chances of restoration failure; subsequently their management will become an ever-increasing challenge to the profession. In cases of Fixed Partial Denture (FPD) supported by multiple abutments or Multiple Connected Full-Coverage Restorations (MCFCR); endodontic/periodontal involvement of even a single abutment negatively affects the prognosis of the prosthesis as a whole. Often the decision made by clinician to remove the fixed bridge or MCFCR, extract the tooth in question and make a new FPD is not appreciated by the patient.  Case discussion: This article describes the technique of a root resection in single rooted teeth, gives new information about its application and analyzes the role of this treatment modality in the management of a failing MCFCR.  Conclusion: Resection of root of single rooted teeth which is not acting as terminal abutment in a multiple-connected full coverage restoration was found to be a successful strategy to prolong the success of a fixed prosthesis.